Management of pneumatosis cystoides intestinalis with pneumoperitoneum: 5-years systematic review. - Piltcher-da-Silva, Rodrigo; Sasaki, Vivian Laís; Gallotti, Felipe Melloto; Saenger, Bruna Freitas; Piltcher-Recuero, Mariana; Rocha, Gabriela de Melo; da Costa, Marco Aurélio Raeder; Coelho, Júlio Cezar Uili (Clinical and Biomedical Research, 2022)
Summary Background: Pneumatosis Cystoides Intestinalis (PCI) is a rare condition, characterized by gas-filled cysts in the intestinal wall. Rarely, it may also involve other places, such as the mesentery. It is classified as primary and secondary and associated with multiple predisposing factors. Its differential diagnosis is mesenteric ischemia. Methods: We conducted a systematic literature review according to PRISMA statement. PubMed and LILACS databases were searched for articles published between January 2015 and December 2020. The subject headings were "Pneumatosis cystoides intestinalis" and "pneumoperitoneum", "pneumatosis intestinalis" and "pneumoperitoneum" or "mesenteric pneumatosis". Results: 51 articles with 58 patients with PCI and pneumoperitoneum were included. Most patients were male and the average age was 64.9 years. The idiopathic etiology was recorded in 29.31% and the most common predisposing factor were immune dysfunction (28.3%). 24.13% were asymptomatic and the most commons symptoms were abdominal pain (43.1%), nausea and vomiting (41.37%) and abdominal distention (37.93%). Diagnostic surgery was performed in 26 patients (44.8%). Just one patient underwent to surgery with treatment intent. Conclusion: PCI is a benign disease that can be confused with a potentially fatal condition, mesenteric ischemia. Treatment is conservative, with periodic clinical evaluations. Surgical procedure is usually not necessary for the diagnosis or management of PCI.